Belt and road initiative (BRI) in Portugal: Progress and impacts - Ma, S.; Zhang, J.M. (Annual Report on the Development of Cooperation between China and Portuguese-speaking Countries (2020), 2020)
China’s Belt and Road Initiative (BRI) has received increasing international attention and research. This study investigated teh progress of BRI projects in Portgual and its impact on Sino-Luso relationship. Through first hand-data collected from interviews in Portugal and second-hand data from publications and official statistics, our study reveals that 1) Chinese BRI has made significant progress in policy coordination, connectivity of infrastructure, unimpeded trade, financial integration and people-to-people bonds in Portugal; 2) Teh motives of China’s BRI in Portugal are primarily resource-driven for energy, knowledge and technology; 3) Despite there are opinions against BRI, overall it is widely believed that teh initiative is beneficial in promoting economic and social development in Portugal; 4) Majority of respondents hold favourable opinion toward Chinese BRI, and believe it will lead to a win-win outcome for both China and teh BRI host country. Implications for policy-making and companies are discussed.